1992
DOI: 10.1002/food.19920360207
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by gamma‐irradiation and antimicrobial food additives of aflatoxin B1 production by Aspergillus flavus in poultry diet

Abstract: SummaryThe effect of gamma-irradiation and the antimicrobial food additives on growth and aflatoxin B, production by A . fluuus NRRL 5520 in poultry diet was investigated. By increasing the irradiation doses the viable population as well as aflatoxin B, production decreased greatly. No growth and no detection of aflatoxin production occurred in poultry diet after treatment with 6 kGy. The addition of the antimicrobial food additives resulted in a significant decrease in aflatoxin B,. Growth and toxin productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Species of Aspergilli, Penicilli, Fusarium, Alternaria, Cladosporium, Helminthosporium, Curvularia, Epicoccum and Verticillium were common and widespread in soil, litter as well as many food and feed ingredients [18,23,24]. A. flavus and A. parasiticus were observed as the main popular fungal species recovered from food and feed in Egypt [3,9,10,25]. only 3 isolates (37.5%) from fababean produced aflatoxin B 1 at levels of 70-100 lg N kg -1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of Aspergilli, Penicilli, Fusarium, Alternaria, Cladosporium, Helminthosporium, Curvularia, Epicoccum and Verticillium were common and widespread in soil, litter as well as many food and feed ingredients [18,23,24]. A. flavus and A. parasiticus were observed as the main popular fungal species recovered from food and feed in Egypt [3,9,10,25]. only 3 isolates (37.5%) from fababean produced aflatoxin B 1 at levels of 70-100 lg N kg -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Factors, such as temperature, moisture, grain type, endogenous fungal species, storage history and length of storage, are known to influence the yield of mycotoxins [3,[7][8][9]. There has been increasing interest in the use of ionizing radiation for killing endogenous and mycotoxigenic microorganisms [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Among the chemical compounds, complete inhibition of mould growth and biosynthesis of aflatoxin is reported at an inclusion of 0.5% of propionic acid was reported by Ghosh et al (1996). El-Far et al (1992) reported complete inhibition of A. flavus growth and aflatoxin production at 0.64% inclusion levels of sodium propionate. Although these mould inhibitors check the fungal growth but their effect on immuno-physiological parameters of fish needs to be thoroughly studied.…”
mentioning
confidence: 87%
“…Each determination was conducted in triplicate and the results were recorded as mean value. Positive samples were further confirmed by reaction with trifluoroacetic acid and by the change to yellow fluorescence with 5% H 2 SO 4 [14].…”
Section: Determination Of Aflatoxinsmentioning
confidence: 97%
“…There has been increasing interest in the use of ionizing radiation, particularly high-energy electron beams for killing endogenous insects and microorganisms in stored cereal grains [5,6,11,14,15,16,18,27,31,32,35,38]. There are number of conflicting reports which suggest that the production of mycotoxins is either increased [28,34], decreased [35,36,38] or unaffected [27] after irradiation of grains or spores under various laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%